Nonlinear Seismic Response Analysis of Curved and Skewed Bridge System with Spherical Bearings - Junwon Seo; Daniel G. Linzell; Jong Wan Hu (Advances in Civil Engineering)
A three-dimensional (3D) modeling approach to investigate nonlinear seismic response of a curved and skewed bridge system is proposed. The approach is applied to a three-span curved and skewed steel girder bridge in the United States. The superstructure is modeled using 3D frame elements for the girders, truss elements for the cross-frames, and equivalent frame elements to represent the deck. Spherical bearings are modeled with zero-length elements coupled with hysteretic material models. Nonlinear seismic responses of the bearings subjected to actual ground motions are examined in various directions. Findings indicate that the bearings experience moderate damage for most loading scenarios based on FEMA seismic performance criteria. Further, the bearing responses are different for the loading scenarios because of seismic effects caused by interactions between excitation direction and radius of curvature.